Assessment-Based Career Development Center and Training Provision: Essence and Indicators of Success - Agus Suhendra; Nuraeni, Nuraeni; Subagio, Mochammad; Yanthy Yosepha, Sri; Murdiono, Jatmiko (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This article delves into the complexities of today's job market and the challenges individuals encounter in career management. It advocates for assessment and training-based career development centers as effective solutions. Through qualitative research and a decade-spanning literature review, it offers insights for practitioners and HR managers to optimize career strategies. The study emphasizes the significance of individualized approaches and highlights the importance of participant engagement in training programs. Overall, it provides valuable guidance for navigating career development amidst evolving workplace dynamics